The most Promising Indian start-ups among world's Top 50 - Mittal, A K (Gyan Management Journal, 2017)
Indian artificial intelligence (AI) start-ups, Bengaluru-based Mihup Communications Pvt. Ltd and Chennai-based Mad Street Den Systems Pvt. Ltd, are among three early-stage local ventures that are on the list of some of the most low-key, yet promising start-ups around the world, according to a Bloomberg report.The emergence of Mihup and Mad Street Den highlights how AI start-ups from India are slowly starting to go mainstream and are among the hottest focus sectors for top venture capital firms such as Acee! Partners and Sequoia Capital. Last year, Mihup raised about Rs45 crore from investors such as Acee!, while Mad Street Den also raised an undisclosed sum in a Series A round from investors led by Segouia Capital.
Keywords: Communications; low-key; start-ups; mainstream